Minimally Invasive Surgery of Pancreatic Cancer: Feasibility and Rationale - Bausch, Dirk (Visc Med, 2018)
Minimally invasive pancreatic procedures, in particular minimally invasive pancreaticoduodenectomy, are amongst the most technically challenging procedures in general surgery. Accordingly, a high number of cases is required to master the procedures. Minimally invasive pancreatic surgery is well established for benign and premalignant lesions of the pancreas. Borderline resectable tumors with infiltration of the portal vein are also resected minimally invasively in specialized centers with appropriate expertise. Retrospective and registry studies demonstrate an equivalent long-term survival compared to conventional surgery. Perioperative morbidity and mortality are also equivalent, whereas minimally invasive surgery significantly reduces hospital stay. We expect more widespread use of minimally invasive pancreatic procedures in large centers.